Implementation and Analysis of the Performance of EDTA (Enhanced Decision Tree Data Mining Algorithm) for diagnosis of Angioplasty and Stents for Heart Disease Treatment - Kaur, Amarjeet; Jetawat, Ashok; Singh, Gurpreet (International Journal of Computer Sciences and Engineering, 2025)
Data mining is a process of extraction of useful information and patterns from huge data. It is also called as knowledge discovery process, knowledge mining from data, knowledge extraction or data pattern analysis. We present a improved approach to support nearest neighbor queries from mobile hosts by leveraging the sharing capabilities of wireless ad-hoc networks. We illustrate how previous query results cached in the local storage of neighboring mobile peers can be leveraged to either fully or partially compute and verify spatial queries at a local host. The feasibility and appeal of our technique is illustrated through extensive simulation results that indicate a considerable reduction of the query load on the remote database.